East Indian Sandalwood Oil (EISO) Alleviates Inflammatory and Proliferative Pathologies of Psoriasis - Sharma, Manju; Levenson, Corey; Clements, Ian; Castella, Paul; Gebauer, Kurt; Cox, Michael E. (Frontiers in Pharmacology, 2017)
Psoriasis, a chronic inflammatory skin disease marked by hyper proliferation and aberrant differentiation of keratinocytes, affects 2-3% of the world’s population. Research into the pathogenesis of psoriasis has been hampered by the lack of models that accurately reflect the biology of the psoriatic phenotype. We have previously reported that “East Indian Sandalwood oil” (EISO) has significant anti-inflammatory properties in skin models and hypothesized that EISO might provide therapeutic benefit to psoriasis patients due to its anti-inflammatory and anti-proliferative properties. Here we present interim results from an on-going proof-of-concept Phase 2 clinical trial in which topically applied EISO is demonstrating to be well tolerated and helpful in alleviating mild to moderate psoriasis symptoms. This led us to evaluate the ability of EISO to affect the psoriatic phenotype using MatTek Corporation reconstituted organotypic psoriatic and normal human skin models. EISO had no impact on the phenotype of the normal skin tissue model, however EISO treatment of the psoriasis tissue model reverted psoriatic pathology as demonstrated by histologic characterization and expression of keratinocyte proliferation markers, Ki67 and psoriasin. These phenotypic affects correlated with suppressed production of ENA-78, IL-6, IL-8, MCP-1, GM-CSF and IL-1β. Demonstration of the ability of EISO to abrogate these psoriasis symptoms in well-characterized in vitro psoriatic tissue models, supports the hypothesis that the clinically observed symptom alleviation is due to suppression of intrinsic tissue inflammation reactions in afflicted lesions. This study presents a systematic approach to further study the underlying mechanisms that cause psoriasis, and presents data supporting the potential of EISO as a new ethnobotanical therapeutic concept to help direct and accelerate the development of more effective therapies.